2024
DOI: 10.1039/d4dt00224e
|View full text |Cite
|
Sign up to set email alerts
|

Copper-based electrocatalyst for hydrogen evolution in water

Abdullah M. Abudayyeh,
Michael S. Bennington,
Johan Hamonnet
et al.

Abstract: In aqueous pH 7 phosphate buffer, during controlled potential electrolysis (CPE) at -1.10 V vs Ag|AgCl the literature square planar copper complex, [CuIILEt]BF4 (1), forms a heterogeneous deposit on the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…It was found that Au, Ag, Cu and other metal clusters with inert H 2 evolution also display unique electrocatalytic H 2 production activity. 40–42 These metal elements feature relatively cheap prices and high earth reserves, making the study of non-platinum metal electrocatalysis even more valuable for HER.…”
Section: Electrocatalytic H2 Productionmentioning
confidence: 99%
“…It was found that Au, Ag, Cu and other metal clusters with inert H 2 evolution also display unique electrocatalytic H 2 production activity. 40–42 These metal elements feature relatively cheap prices and high earth reserves, making the study of non-platinum metal electrocatalysis even more valuable for HER.…”
Section: Electrocatalytic H2 Productionmentioning
confidence: 99%